Faktor yang Berhubungan dengan Lokasi Osteoarthritis Genue pada Pasien Usia Lanjut di RS Ibnu Sina Tahun 2021-2024 - Syahrul Adnan; Syarifuddin Wahid; Berry Erida Hasbi; Fadil Mula Putra; Muh Jabal Nur (Wal'afiat Hospital Journal, 2025)
Factors Associated with the Location of Osteoarthritis Genue in Elderly Patients at Ibnu Sina Hospital in 2021-2024. Osteoarthritis is a common form of arthritis in geriatric populations that can cause damage to the bones and their surroundings. There are several things that are risk factors for Osteoarthritis. This study aims to make observations related to factors that can affect the occurrence of Osteoarthritis in the elderly, the data used is the patient's medical records recorded in the hospital. This study uses the cross-sectional study method. Univariate or characteristic analysis uses frequency distribution analysis and bivariate analysis or analysis of relationships between variables using the chi-square test. The results of the study showed that there was an effect of disease history on the risk of osteoarthritis in the elderly. Hypertension is one of the risk factors that can increase the incidence of osteoarthritis, especially in men, this is related to the activity of endogenous receptors (AR) in the Renin-angiotensin-aldosterone system.